Pengaruh Product Innovation, Celebrity Endorsment dan Fear of Missing Out (FOMO) Terhadap Purchase Decision: Studi pada Pembeli Boneka Labubu Di Surabaya - Afidahzulfa; Raya Sulistyowati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The phenomenon of high interest in limited edition collection products such as Labubu dolls has encouraged the emergence of marketing strategies based on innovation, celebrity promotion, and consumer psychological effects. This study aims to determine the effect of product innovation, celebrity endorsement, and Fear of Missing Out (FOMO) on purchasing decisions of Labubu doll buyers in Surabaya City. This study uses a quantitative approach with an explanatory type that aims to explain the relationship between variables through hypothesis testing. The number of samples was determined based on the Rambut formula with a total of 100 respondents selected using the purposive sampling method. Data analysis was carried out with the help of SmartPLS 4 software. The results of the study showed that partially, the third independent variable, namely product innovation, celebrity endorsement, and Fear of Missing Out (FOMO) had a positive and significant effect on purchasing decisions. Simultaneously, all three also had a significant effect on consumer decisions. This study shows that the combination of the appeal of innovative products, promotion through public figures, and psychological pressure not to be left behind by trends are important factors in driving purchasing decisions on collectible doll products.